2014
DOI: 10.1182/blood-2014-05-574889
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations identify a subgroup of aplastic anemia patients who progress to myelodysplastic syndrome

Abstract: Key Points• Acquired mutations of myeloid-related genes are present in a proportion of AA patients.• Somatic mutations in AA predict higher risk of transformation to MDS.The distinction between acquired aplastic anemia (AA) and hypocellular myelodysplastic syndrome (hMDS) is often difficult, especially nonsevere AA. We postulated that somatic mutations are present in a subset of AA, and predict malignant transformation. From our database, we identified 150 AA patients with no morphological evidence of MDS, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
229
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(236 citation statements)
references
References 37 publications
4
229
1
2
Order By: Relevance
“…8 More recently, the issue has been newly addressed by using revolutionized sequencing technologies, unmasking a unique picture of CH in AA frequently accompanied by somatic mutations commonly seen in myeloid malignancies. [13][14][15][16][17][18] Combined with seminal findings on CH in aged normal individuals, [19][20][21] as well as on preleukemic clones 22 in patients with hematologic malignancies, [23][24][25] the finding on somatic mutations in AA provides new insight into the origin and the mechanism of frequent CH in AA and its impact on the late development of MDS and AML. 13,15,18 This review summarizes recent progress in the current understanding of CH in AA in relation to the pathogenesis of late clonal diseases.…”
Section: Medscape Continuing Medical Education Onlinementioning
confidence: 92%
See 4 more Smart Citations
“…8 More recently, the issue has been newly addressed by using revolutionized sequencing technologies, unmasking a unique picture of CH in AA frequently accompanied by somatic mutations commonly seen in myeloid malignancies. [13][14][15][16][17][18] Combined with seminal findings on CH in aged normal individuals, [19][20][21] as well as on preleukemic clones 22 in patients with hematologic malignancies, [23][24][25] the finding on somatic mutations in AA provides new insight into the origin and the mechanism of frequent CH in AA and its impact on the late development of MDS and AML. 13,15,18 This review summarizes recent progress in the current understanding of CH in AA in relation to the pathogenesis of late clonal diseases.…”
Section: Medscape Continuing Medical Education Onlinementioning
confidence: 92%
“…15 Excluding PIGA mutations, somatic mutations were detected in 29 of 150 (19.3%) patients. In accordance with Yoshizato et al's report, mutations were more frequently observed in older patients and in those having longer (.6 months) disease durations.…”
Section: Skewed X-chromosome Inactivationmentioning
confidence: 99%
See 3 more Smart Citations